Development of Biliary and Enteral Stents by the Korean Gastrointestinal Endoscopists - Chan Sup Shim; Jin Hong Kim; Gene Hyun Bok (Korean Society of Gastrointestinal Endoscopy, 2016)
Stenting in the gastrointestinal tract is a common procedure used for palliation of obstruction in the enteral and biliary tract. Today, stenting of malignant and benign strictures is performed at almost every major tertiary hospital in Korea. Moreover, Korea has become a major global supplier of cutting edge technology in the field of self-expanding metal stents. However, the history of stenting in Korea is relatively short and was far behind that of other nations such as Japan and Germany. The authors are humbled and gratified to have been able to observe the development and application of these stents in Korea, first hand. In this article, the authors review the overall history of stenting with a specific focus on the development of stenting in Korea. The development of esophageal, gastroduodenal, biliary, and colonic stents in Korea are reviewed in this article from a chronological and historical point of view, and a personal account of some of the significant moments of stent development in Korea are described.